2019
DOI: 10.2147/idr.s193712
|View full text |Cite
|
Sign up to set email alerts
|

<p>Simulating moxalactam dosage for extended-spectrum β-lactamase-producing <em>Enterobacteriaceae</em> using blood antimicrobial surveillance network data</p>

Abstract: Objectives: Monte Carlo simulation (MCS) was used to evaluate optimal dosage for cefepime (FEP), moxalactam (MOX), and cefperazone/sulbactam (CFZ/SBT) against extended-spectrum β-lactamase (ESBL) producers isolated from the Blood Bacterial Resistant Investigation Collaborative System. Methods : Minimum inhibitory concentration (MIC) was tested by agar dilution, and ESBL producers were identified by modified Clinical and Laboratory Standards Institute tests. Pharmacokinetic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The purpose of this mini review was to briefly survey the techniques and decisions researchers made while performing cefepime PTA. Therefore, only the first 20 titles were reviewed, of which 14 met the inclusion criteria of a PTA study, with at least one evaluation of cefepime alone in adult patients ( Table 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. A study by Das et al was excluded because cefepime was studied in combination with a novel beta-lactamase inhibitor, changing the risk benefit from cefepime alone [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The purpose of this mini review was to briefly survey the techniques and decisions researchers made while performing cefepime PTA. Therefore, only the first 20 titles were reviewed, of which 14 met the inclusion criteria of a PTA study, with at least one evaluation of cefepime alone in adult patients ( Table 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. A study by Das et al was excluded because cefepime was studied in combination with a novel beta-lactamase inhibitor, changing the risk benefit from cefepime alone [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The MIC of interest was generally set at 8 mg/dL, consistent with the breakpoint defined by the Clinical and Laboratory Standards Institute against pseudomonas aeruginosa [ 35 ]. Success was commonly defined as PTA > 90% against a given MIC; however, some authors defined success as CFR > 90% against an observed MIC distribution [ 18 , 20 , 21 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, infections caused by the multidrug-resistant extended-spectrum β-lactamase (ESBL)-producing Enterobacterales (ESBL-E) have become a serious issue in companion animals, as well as in humans [1,2]. Carbapenems are frequently used for the treatment of ESBL-E infections in human medicine but there is a risk of developing carbapenem-resistant Enterobacterales (CRE) [3,4]. Although the true prevalence of CRE in companion animals is unknown, there have been several reports on CRE isolation in dogs and cats worldwide [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Plasmids encoding ESBLs often carry resistance genes for different classes of antimicrobials; therefore, ESBL-E have developed multidrug resistance with high resistance against β-lactams and other classes of antimicrobials, thus limiting the number of effective antimicrobial agents available for treatment ( 1 ). Carbapenems are recommended as the first-line drugs for treating ESBL-E infections in humans but not in animals owing to the risk of developing carbapenemase-producing Enterobacteriaceae (CPE), which is a more serious threat than ESBL-E ( 4 , 5 ). Therefore, the use of carbapenems is discouraged in veterinary medicine due to the potential risk of zoonotic transmission from companion animals to humans through close contact ( 6 ).…”
Section: Introductionmentioning
confidence: 99%